The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.7150/ijms.31669
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Anterior Stromal Puncture Surgery with Corneal Bandage Lens for Bullous Keratopathy

Abstract: Objective: To investigate the safety and efficacy of the combination therapy of anterior stromal puncture (ASP) with bandage contact lens for bullous keratopathy (BK). Methods: Twelve cases (12 eyes) with vision acuity no better than light perception were treated with ASP surgery and bandage contact lens. 200 points punctures were made through the corneal epithelium and Bowman's layer vertically, using fine needles. A soft bandage contact lens was applied immediately and remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Studies show that when combined, sodium hyaluronate, tobramycin, dexamethasone, and pranoprofen act synergistically to reduce the ocular inflammatory response and shorten the incision healing time, thus keeping the eyes moist, promoting corneal and conjunctival repairs, and improving the ocular circulation, to achieve an optimal curative effect. [ 26 27 ] Consistently with these observations, we found that the addition of sodium hyaluronate to the post-phacoemulsification treatment regimen was associated with a markedly improved effective rate in patients with postoperative dry eye. Moreover, it resulted in an over 1.8-fold increase in the rate of complete cure as compared to patients who received the conventional treatment with tobramycin, dexamethasone, and pranoprofen only.…”
Section: Discussionsupporting
confidence: 74%
“…Studies show that when combined, sodium hyaluronate, tobramycin, dexamethasone, and pranoprofen act synergistically to reduce the ocular inflammatory response and shorten the incision healing time, thus keeping the eyes moist, promoting corneal and conjunctival repairs, and improving the ocular circulation, to achieve an optimal curative effect. [ 26 27 ] Consistently with these observations, we found that the addition of sodium hyaluronate to the post-phacoemulsification treatment regimen was associated with a markedly improved effective rate in patients with postoperative dry eye. Moreover, it resulted in an over 1.8-fold increase in the rate of complete cure as compared to patients who received the conventional treatment with tobramycin, dexamethasone, and pranoprofen only.…”
Section: Discussionsupporting
confidence: 74%
“…ASP was first used in the treatment of RCE in 1986 by McLean et al( 8 ) and comparative studies have been conducted to evaluate the effectiveness of this procedure, alone or in combination with other treatment options ( 5 , 9 - 11 ). Despite successful reports of ASP for RCE, the mechanism of how the procedure works on the cellular level is still unknown, and there are only few reports on the process of healing with ASP; a study reported in 1990 investigated the healing process after ASP by electron microscopy in rabbit corneas with recurrent erosion ( 12 ).…”
Section: Introductionmentioning
confidence: 99%